2019
DOI: 10.18844/cjes.v14i2.3714
|View full text |Cite
|
Sign up to set email alerts
|

Self-esteem, hopelessness and communication skills in preschool teacher candidates: A mediation analysis

Abstract: The goal of this study is to investigate the relation of self-esteem, hopelessness and communication skill; while testing self-esteem as an intermediary variable. The research, designed in survey model, has been conducted with preschool teacher candidates. The research group comprises 305 teacher candidates that volunteered for the research. According to the findings of the research, teacher candidates’ self-esteem is negatively correlated with their level of hopelessness and positively correlated with their c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In distinguishing hopelessness from depression, many studies have also shown that the severity of suicidal intent appears to be more strongly related to hopelessness than depression and that hopelessness can lead to suicidal ideation or behavior [31][32][33][34][35][36][37][38]. The identification of hopeless individuals may be considered a "red flag" in helping professions such as nurses [39], physicians [40], teachers [41], and police officers [42] and should encourage preventive measures.…”
Section: Hopelessness Depression Burnout and Suicide Risk In Police O...mentioning
confidence: 99%
“…In distinguishing hopelessness from depression, many studies have also shown that the severity of suicidal intent appears to be more strongly related to hopelessness than depression and that hopelessness can lead to suicidal ideation or behavior [31][32][33][34][35][36][37][38]. The identification of hopeless individuals may be considered a "red flag" in helping professions such as nurses [39], physicians [40], teachers [41], and police officers [42] and should encourage preventive measures.…”
Section: Hopelessness Depression Burnout and Suicide Risk In Police O...mentioning
confidence: 99%
“…In that context, therefore, effective relationship-building and communication skills emerge as key dimensions of classroom management (Martin & Sass, 2010;Şahin-Sak et al, 2018b); and as such, it is vital that preservice teachers, as the teachers of the future, are well-equipped with them. Moreover, positive influences of effective communication skills on several other skills of in-service and preservice teachers have been reported by various studies (Duta et al, 2015;Erkan & Avcı, 2014;Tepeli & Arı, 2011;Uyanık Balat et al, 2019).…”
Section: Discussionmentioning
confidence: 95%
“…It may have negative impacts on people's mental health, resulting in issues including depression and suicide ideation (Boduszek & Dhingra, 2016;Waheed et al, 2022). Hopelessness has a negative impact on teachers' self-esteem, communication abilities, and overall job effectiveness (Balat, et al, 2019).…”
Section: Introductionmentioning
confidence: 99%